The Impact of Corporate Social Responsibility and Investment Opportunity Set on Firm Value: The Moderating Role of Good Corporate Governance - Suryadi, Nanda; Yusnelly, Arie; Musa, Sulaiman (Research in Accounting Journal (RAJ), 2024)
This study aims to provide empirical evidence on the influence of Corporate Social Responsibility (CSR) and Investment Opportunity Set (IOS) on Firm Value, with Good Corporate Governance (GCG) as a moderating variable in state-owned enterprises (SOEs) listed on the Indonesia Stock Exchange (IDX) during the 2018–2022 period. The research population consists of all SOEs listed on the IDX within the specified period. A purposive sampling method was employed, using specific criteria determined by the researcher, resulting in a sample of 14 companies out of a total of 24. The hypotheses in this study were tested using the Outer Model and Inner Model through the SmartPLS v3.0 software. The results of the study conclude that Corporate Social Responsibility has no significant effect on Firm Value, while the Investment Opportunity Set does have a significant impact on Firm Value. Furthermore, Good Corporate Governance strengthens the relationship between Corporate Social Responsibility and Firm Value, but does not moderate the relationship between the Investment Opportunity Set and Firm Value.